Pengaruh Motivasi, Disiplin Belajar, dan Kemampuan Berpikir Kritis terhadap Hasil Belajar Siswa - Safna, Oktaviangga Putri; Wulandari, Siti Sri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to determine the effect of motivation, learning discipline, and critical thinking skills on student learning outcomes at SMKN 2 Buduran Sidoarjo. The population of this research is using class XI and class XII students of SMKN 2 Buduran Sidoarjo, totaling 146 students. The sample used is as many as 106 respondents with probability sampling technique in the sample selection, namely by simple random sampling. The data collection technique used primary data in the form of questionnaires and secondary data using interviews, observations, and the results of the final assessment of the odd semester 2021/2022. The scale used in this study is a Likert scale using Structural Equational Modeling-Partial Least Square (SEM-PLS) data analysis for the software used, namely SmartPLS version 3.0 using the Outer Model and Inner Model stages. The results obtained from this study are that motivation has no significant effect on student learning outcomes as indicated by the t-statistic 1.305 > 1.96 and p-value 0.192 > 0.05; learning discipline also has no significant effect on student learning outcomes seen from the t-statistic 0.100 1.96 and p-value 0.920 greater than 0.05. On the other hand, critical thinking ability is stated to have a significant effect on student learning outcomes in terms of t-statistic 10.211 > 1.96, also p-value of 0.000 <0.05.